2006
DOI: 10.1097/01.rmr.0000245455.59912.40
|View full text |Cite
|
Sign up to set email alerts
|

High-field Magnetic Resonance Imaging of Brain Iron in Alzheimer Disease

Abstract: A large number (163) of features from these histograms were examined, and 38 of these were significantly different (P < 0.05) between the groups. In the hippocampus, evidence was found for AD-related increases in iron deposition (shortened T2) and in the concentration of free tissue water (lengthened T2). Imaging of a section of postmortem brain before and after chemically extracting the iron established the presence of MRI-detectable iron in the hippocampus, cortex, and white matter in addition to brain regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 82 publications
2
54
0
Order By: Relevance
“…20) and was confirmed with an iron extraction study (22). However, contributions from other sources have prevented the quantification of tissue iron content directly from the MRI measures.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…20) and was confirmed with an iron extraction study (22). However, contributions from other sources have prevented the quantification of tissue iron content directly from the MRI measures.…”
Section: Discussionmentioning
confidence: 59%
“…One way to address this question is to selectively manipulate tissue iron content and observe the effects on MRI contrast. Using a biochemical process to extract iron from postmortem tissue, Schenck and coworkers previously found that iron substantially affects R 2 * relaxation in much of the brain (22). Applying their protocol to primary visual cortex, we observed an almost complete extinction of intracortical R 2 * and frequency contrasts ( Fig.…”
Section: Reduction Of Mri Contrast After Chemical Extraction Of Tissumentioning
confidence: 63%
See 1 more Smart Citation
“…One way to establish quantitatively the contribution of iron would be to perform MR imaging before and after chemical extraction of iron. We and others have done this in normal tissue for gray matter and WM ( 28,29 ). Despite the lack of these derived measures of tissue iron ( 12,20 ), have suggested that iron and myelin are the main compounds that contribute to the R2* and phase contrast in WM and cortical gray matter.…”
Section: Neuroradiology: High-field-strength Mr Imaging Of Chronic Mumentioning
confidence: 99%
“…This hypothesized diamagnetic shift associated with myelin proposed in our model is consistent with recent high-fi eld-strength MR imaging observations in the line of Gennari, a myelin-rich layer in human primary visual cortex ( 28 ), and the absence of phase contrast between cerebrospinal fl uid and WM in this and previous work ( 11 ), despite the strongly different iron and myelin concentrations of the two substances. Results of number of recent studies, including iron extraction studies ( 28,29 ), demyelinating animal models with shiverer mice ( 30 ) and cuprizone-treated mice ( 31 ), and correlative studies between MR imaging and histochemically This heterogeneity was present across and in some cases within lesions. Consistent with previous work ( 9 ), lesions with and without pronounced rim contrast were observed.…”
Section: Neuroradiology: High-field-strength Mr Imaging Of Chronic Mumentioning
confidence: 99%